10-Year Trends in Epidemiology, Diagnosis, and Treatment of Cutaneous Leishmaniasis in Hamadan Province, West of Iran (2007–2016) - Akhlagh, Azita; Salehzadeh, Aref; Zahirnia, Amir Hossein; Davari, Behrooz (Frontiers in Public Health, 2019)
Background: Cutaneous leishmaniasis is one of the most important infectious diseases in eastern Mediterranean countries. The aim of this study was to determine the epidemiological pattern of cutaneous leishmaniasis across a 10-year period in the Hamadan province. This study was considered necessary due to the lack of new information in recent years on the epidemiology of the disease. Methods: This is a descriptive study. The data of patients who were diagnosed with cutaneous leishmaniasis in Hamadan health centers were collected during 10 years (2007–2016) and were analyzed using SPSS software. Results: Of the 908 registered patients, 94% were male and 6% were female. The mean age was 32.7 ± 11.8. About 87.1% of patients had a history of travel to endemic areas. The highest incidence rate was observed in the year 2015 with a rate of 12.6, and the lowest was in 2008 at 1.5 per 100,000 people. Conclusion: Due to an increasing trend in the number of cutaneous leishmaniasis in Hamadan and the effect of occupation, high-risk groups such as lorry drivers should be informed of preventive measures such as using insect repellents. Also, considering the possibility of shaping a new hotspot in the province, thorough reviews and more comprehensive entomological studies are recommended.